1973
DOI: 10.1002/aic.690190415
|View full text |Cite
|
Sign up to set email alerts
|

Momentum transfer through packed beds of various particles in the turbulent flow regime

Abstract: The flow of air through packed beds of solid and hollow particles of a wide range of geometries was studied, with particular reference to the effect of the particle shape on the pressure drop in the turbulent range. A method of analysis based on the concept of stagnant void fraction and the principle of drag additivity has been developed. Equations for estimating the stagnant voidages for various particle shapes arranged in a random pattern in a packed bed were derived. A new type of friction factor based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…It follows that the use of this equation, or the use of relation-ships derived from it, becomes questionable when applied to distances that are comparable to the size of the particles that make up the packing. Another important limitation of the Ergun equation, as cited by Gauvin and Katta (1973), is the fact that it is not appropriate for systems containing partides of low sphericity.…”
Section: Discussionmentioning
confidence: 99%
“…It follows that the use of this equation, or the use of relation-ships derived from it, becomes questionable when applied to distances that are comparable to the size of the particles that make up the packing. Another important limitation of the Ergun equation, as cited by Gauvin and Katta (1973), is the fact that it is not appropriate for systems containing partides of low sphericity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, for a sphere / = 1, and for non-spherical particles 0 < / < 1. Many experimental and modeling studies have been conducted to find a correlation between bed voidage and particle properties [15,[18][19][20][21][22][23]. These studies have shown that voidage of a packed bed depends not only on particle sphericity but also on several other factors including particle size and PSD, surface roughness, method of packing, and Nomenclature A, B constants in Eq.…”
Section: Influence Of Particle Sphericitymentioning
confidence: 99%
“…Each cell contains a particle surrounded by a fluid envelope, ie , the entire influence due to each particle is confined to the cell of fluid with which it is associated. See for an evaluation of this class of models [114,117] and also the recently proposed model of Neale and Nader [43,334], which predicts JD and k for random sphere packings solely as a function of e and d.…”
Section: Empirical Correlationsmentioning
confidence: 99%